End‐Group Functionalization of Non‐Fullerene Acceptors for High External Quantum Efficiency over 150 000% in Photomultiplication Type Organic Photodetectors. (28th September 2020) - Yoon, Seongwon; Lee, Gyeong Seok; Sim, Kyu Min; Kim, Myeong‐Jong; Kim, Yun‐Hi; Chung, Dae Sung
Abstract: Photomultiplication‐type organic photodetectors (PM‐OPDs) with high external quantum efficiency (EQE) of over 100% are attracting increasing attention due to their potential importance in detecting weak incident light. Considering that the gain of PM‐OPD is determined by the ratio of carrier lifetime over carrier transit time, a systematic study on the effect of the end‐functionalization of a new extended aromatic fused‐ring non‐fullerene acceptor (NFA) on the carrier trap/transit time of the PM‐OPD. Photophysical analyses by means of ultraviolet‐visible absorption, ultraviolet photoelectron spectroscopy, and photoluminescence combined with structural analyses through grazing‐incidence wide‐angle X‐ray scattering show that fluorination of the NFA with the deepest lowest unoccupied molecular orbital level and non‐isotropic molecular ordering can yield the longest carrier lifetime. Furthermore, surface energy study show that fluorination of the NFA can also yield the most hydrophobic nature, which can allow the most efficient injection barrier thinning/lowering of the active layer/cathode interface under illumination due to the localized acceptor distribution toward cathode, maximizing the hole injection efficiency from cathode. As a result, an unprecedentedly high EQE of 156 000% is obtained from the optimized PM‐OPD. This work shows the importance of the molecular design of acceptor molecules in fabricating high‐performance PM‐OPDs. Abstract : A series of new non‐fullerene acceptors (NFAs) with a large fused aromatic system are synthesized and used as electron‐trapping acceptors for realizing high‐performance photomultiplication‐type organic photodetectors (PM‐OPDs). The end‐functionalization of the extended fused‐ring NFA significantly affect the charge carrier lifetime of the resulting PM‐OPDs and preferentially focused acceptor distribution. Consequently, an unprecedentedly high external quantum efficiency over 150 000% is achieved.